Line of duty. Series 4 [videorecording (DVD)]. - Newton, Thandiwe, 1972-; Ingleby, Lee; Compston, Martin; McClure, Vicky, 1983- (Acorn, 2017)
In the thick of a career-defining case, Roz is under intense pressure to prove herself to her superiors. But when she faces conflict with a colleague, it's not long before AC-12 decide to probe her handling of the investigation.